Answer :

x2 - 6x + 5 = 0

The equation is of the form ax2 + bx + c = 0


Since a≠0 ,so it exists


We use the method of factorization to solve it


x2 - 5x - x + 5 = 0


x(x - 5) - 1(x - 5) = 0


(x - 1)(x - 5) = 0


x = 1,5


Rate this question :

How useful is this solution?
We strive to provide quality solutions. Please rate us to serve you better.
Try our Mini CourseMaster Important Topics in 7 DaysLearn from IITians, NITians, Doctors & Academic Experts
Dedicated counsellor for each student
24X7 Doubt Resolution
Daily Report Card
Detailed Performance Evaluation
caricature
view all courses
RELATED QUESTIONS :

<span lang="EN-USAP- Mathematics

<span lang="EN-USAP- Mathematics

<span lang="EN-USAP- Mathematics

<span lang="EN-USAP- Mathematics

<span lang="EN-USAP- Mathematics

<span lang="EN-USAP- Mathematics

<span lang="EN-USAP- Mathematics

<span lang="EN-USAP- Mathematics

<span lang="EN-USAP- Mathematics

<span lang="EN-USAP- Mathematics